Implementasi Program Adiwiyata Di SMP Negeri 2 Cilongok Dan Relevansinya Terhadap Karakter Religius Siswa - Liana Putri, Intan; Nur Azizah, Intan (Jurnal Pendidikan Agama Islam, 2025)
Islamic Religious Education plays a crucial role in shaping students' religious character. The Adiwiyata Program, as an environmental initiative, is expected to integrate religious values and environmental awareness, thereby creating students who are not only concerned about the environment but also possess good moral character within the context of education in Indonesia. This study aims to describe the implementation of the Adiwiyata Program at SMP Negeri 2 Cilongok Banyumas and its relevance to students' religious character. The type of research conducted is field research using a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions/data verification. Based on the methods used, the research results indicate that the Adiwiyata Program at SMP Negeri 2 Cilongok Banyumas is related to students' religious character. The implementation of the Adiwiyata Program begins with planning, implementation, and evaluation. The implementation of the Adiwiyata Program at SMP Negeri 2 Cilongok Banyumas is related to students' religious character, which includes love for the environment, cooperation, and an environmentally friendly attitude (anti-violence), as evidenced by the Zero Plastic program and planting activities that foster love for the environment as a manifestation of preserving God's creation. Additionally, the Clean Friday activity serves as a tangible manifestation of religious teachings on mutual aid and cooperation in goodness. The healthy canteen initiative, which encourages the use of personal containers, aligns with religious commands to preserve, not damage, and be environmentally friendly. Overall, Adiwiyata is closely related to students' religious character.